Tubeimoside I Antagonizes Yoda1-Evoked Piezo1 Channel Activation - Liu, Silin; Pan, Xianmei; Cheng, Wenbin; Deng, Bo; He, Yu; Zhang, Lei; Ning, Yile; Li, Jing (Frontiers in Pharmacology, 2020)
The mechanosensitive Piezo1 channels play roles in a wide range of biological processes, but its pharmacology is in its infancy. In this study, we sought to identify new Yoda1-dependent Piezo1 inhibitors. Intracellular Ca2+ measurements were made in HUVECs, HEK 293T cells overexpressing TRPC5 and TRPM2 channels, CHO K1 cells overexpressing TRPV4 channels, murine liver endothelial cells (MLECs), and macrophages. HEK 293T cells were transfected with a plasmid encoding GFP-tagged wild-type Piezo1. Isometric tension was recorded in mouse thoracic aorta rings. TBMS1 can strongly inhibit Yoda1 response, and its selectivity to Piezo1 channels was determined. The physiological responses of TBMS1 were identified by isometric tension, which can inhibit Yoda1 relaxation of aortic rings. Similarly, Yoda1-induced inhibitory results were obtained in Piezo1 wild-type overexpressed cells, MLECs, and macrophages. TBMS1 can effectively antagonize Yoda1 induced Piezo1 channel activation. This study sheds light on the existence of Yoda1 inhibitors and improves the understanding of vascular pharmacology through Piezo1 channels.